PELANGGATAN KONVENSI JENEWA TENTANG PENYERANGAN FASILITAS DAN TENAGA MEDIS DI KONFLIK SUDAN TAHUN 2021-2024 - Cantika, Fazila Dara Cantika; Wicaksa, Arif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the causes of violations of the 1949 Geneva Convention regarding the protection of medical personnel and facilities during armed conflict in Sudan from 2021-2024. Although Sudan already ratified Geneva Convention in 1957 and apply this convention’s law in their domestic regulation, Law on the Protection of Doctors, Medical Staff and Health Establishments in 2020, the attacks on medical personnel and facilities continue. Sudan is experiencing a complex conflict, starting with a military coup in October 2021, communal conflicts that still occur to this day in Darfur and South Kordofan, and the outbreak of armed conflict between Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF) in April 2023, which triggered a widespread humanitarian crisis and the collapse of health services. This study uses qualitative research based on study literature, and Abram Chayes dan Antonia Handler Chayes’s compliance theory in order to analyze Sudan's noncompliance with the values in 1949 Geneva Convention about the Improvement of the Condition of Wounded and Sick Members of Armed Forces in the Field. The results of this study explain that weak governance and security, which prevent the state from performing its duties effectively, an economic crisis that results in a lack of state funds to finance criminal punishment, and the collapse of the administrative and judicial systems are the main factors behind the failure to enforce laws on the protection of medical personnel and facilities. Keyword: Geneva Convention, War Crime, Compliance Theory.